Impact of employee job attitudes on ecological green behavior in hospitality sector - Muhammad Arshad; Ghulam Abid; Jamil Ahmad; Leena Anum; Mumtaz Muhammad Khan (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Notwithstanding the significant contribution made by employees towards addressing environmental issues, few research studies have explored this important contemporary theme in the hospitality sector. Drawing on the theory of planned behavior (TPB), this research examines the direct and interactive effects of employee environmental job attitudes and behaviors on ecological practices. Using PROCESS Macros on an actual convenient sample of 508 employees working in the hospitality industry, the results show a mixture of anticipated and surprising outcomes. The anticipated outcome is associated with the direct effects of environmental attitude on ecological behavior, while surprising outcomes are in the interaction of job attitudes and behavior (customer-oriented discretionary behavior, organizational commitment). These outcomes provoke employees' green behavior and contentment with the organization. The originality of this research is to investigate the significant contribution of employees in greening the hospitality sector in an emerging economy.
Keywords: 650; customer-oriented OCB; ecological behavior; employee satisfaction; environmental intent; organizational commitment